GRATIFICATION OF PHARMACY COMPANIES AGAINST DOCTORS IN MEDICAL SERVICES IN HOSPITAL - Lismayani, Erika; Rachman, Amelia; Negara, Candra Kusuma (Sean Institute, 2022)
Every industry in today's world, including the medical and health sectors, offers rapid gratification. The existence of retaliation by pharmaceutical companies against doctors, particularly when the pharmaceutical company colludes with doctors to promote drugs by paying them commissions or incentives for each prescription they write for patients when there is a mutually agreed-upon arrangement between the two parties. The conspiracy idea comes from the doctor's request and the pharmaceutical industry. This is also a result of monopolistic practices between pharmaceutical companies and doctors, which cause the price of drugs that patients must purchase to become uncontrollably expensive and raises concerns about the quality of the medications for the patient's recovery because of the doctor's financial incentives to see that the drug is quickly sold/sold on the market. The approach of this study is a type of normative juridical research that employs literature sources, pertinent laws and regulations, other media materials, and interviews to collect information or theories regarding the outcome of the research issue. Pharmacies exert influence by giving something to doctors who work for the government to keep them from losing their freedom and independence when prescribing pharmaceuticals to patients. Doctors routinely recommend pharmaceutical companies' prescriptions because they find it rewarding; as a result, the cost of pharmaceuticals rises, monopolies form, and consumer protection is necessary. It can be considered a crime of gratification for the doctor, which is prohibited under Criminal Code Article 12B.